1992
DOI: 10.1128/jb.174.16.5406-5413.1992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanical removal of pili on gliding motility of Myxococcus xanthus

Abstract: Gliding motility of Myxococcus xanthus is governed by both the adventurous (A) and the social (S) motility gene systems. The presence of pili has previously been shown to be correlated with a genetically intact S-motility system (D. Kaiser, Proc. Natl. Acad. Sci. USA 76:5952-5956, 1979). The purpose of the present work was to study the direct effect of mechanical removal of pill on the social motility of M. xanthus. Depiliation resulted in (i) a loss of streaming motility of A- S+ mutants, i.e., strains which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
(24 reference statements)
2
22
0
Order By: Relevance
“…Pili were intentionally sheared off DK10469 cells by passage through a needle 50 times as previously described (39), except that a 25-gauge 7.5-cm spinal needle was used. Effectiveness of shearing was confirmed by electron microscopy, which showed a reduction in piliated cell ends to 1 to 3% (versus 30 to 40% for unsheared cells).…”
Section: Methodsmentioning
confidence: 99%
“…Pili were intentionally sheared off DK10469 cells by passage through a needle 50 times as previously described (39), except that a 25-gauge 7.5-cm spinal needle was used. Effectiveness of shearing was confirmed by electron microscopy, which showed a reduction in piliated cell ends to 1 to 3% (versus 30 to 40% for unsheared cells).…”
Section: Methodsmentioning
confidence: 99%
“…Kaiser further described fimbriae as 10-nmlong polar appendages that were associated with social motility (22). Rosenbluh and Eisenbach confirmed that, while not required for the maintenance of cell-cell cohesions, pili appear to be involved in the coordination of the movement of cells translocating as groups (social motility) (35). Unlike fibrils (see below), fimbriae are expressed constitutively on cells grown at low densities and in liquid culture (35).…”
mentioning
confidence: 97%
“…No mutant lacking pili retains social motility (21,56). Social motility is also lost when pili are detached by violent shearing and reappears when pili are allowed to grow back (41). Several social motility genes, including tgl (transient glider), the subject of this paper, are needed for production of pili.…”
mentioning
confidence: 99%